A method of depositing solder on a micro LED drive circuit board copper pad
Patent Information
- Application Number
- CN202611004664.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-07
- Publication Date
- 2026-10-09
AI Technical Summary
若选用链长过短的自组装单分子层,则膜层致密性不足,镀液中的金属离子易穿透阻挡层导致非焊盘区域漏镀;若选用链长过长的自组装单分子层,则在微间距下分子层易发生边缘搭接,导致相邻铜焊盘之间的短路风险增加
[0036](1)本发明采用在基板表面整面涂覆自组装单分子层,并通过酸洗选择性去除铜焊盘区域的自组装单分子层,保留非焊盘区域的自组装单分子层作为选择性阻挡层,随后利用化学镀锡液在铜焊盘表面直接沉积锡镀层。该工艺无需物理掩模版与对准工序,从根本上避免了掩模版开窗与铜焊盘的对准偏差问题,简化了工艺步骤,降低了掩模版制造与对准设备的成本,同时消除了开窗尺寸缩小导致的锡膏填充不均缺陷,提升了微间距铜焊盘上锡焊料沉积的工艺良率。
Smart Images

Figure CN122879685A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a method for depositing tin solder on copper pads of a Micro LED driver circuit board. Background Technology
[0002] As display technology advances towards higher resolution and higher brightness, Micro LED display technology, with its advantages such as micron-level pixel size, high contrast, and long lifespan, is considered the next-generation mainstream display technology. In the manufacturing process of Micro LED display devices, micron-level LED chips need to be assembled onto copper pads on the driver circuit board using a soldering process to form reliable electrical connections and mechanical fixation. The quality of the solder deposition on the copper pad surface directly determines the reliability of chip soldering and the yield of the display device.
[0003] Currently, the industry commonly uses solder paste mask printing technology to deposit solder on the copper pads of driver circuit boards. This process involves covering the driver circuit board with a mask featuring a specific window pattern, uniformly brushing solder paste onto the mask surface, ensuring that the solder paste is deposited only on the copper pads directly opposite the window, and then forming a tin plating layer through thermal reflow. However, as the pixel size of Micro LEDs continues to shrink, the pixel pitch between adjacent copper pads has decreased to the tens of micrometers. At this microscale, the window size of the mask decreases accordingly, drastically increasing the alignment accuracy requirements between the mask and the copper pads. Even slight deviations can lead to solder paste misalignment or missing areas. Simultaneously, the reduced window size significantly decreases the uniformity of solder paste filling within the window, easily resulting in uneven solder paste coating, insufficient solder, or bridging defects, leading to a substantial decrease in process yield.
[0004] Chemical tin plating, a wet deposition process that requires no external power supply, can uniformly deposit tin plating on metal surfaces and has mature applications in fields such as printed circuit board surface treatment. However, traditional chemical tin plating processes deposit tin across the entire surface, lacking selectivity for specific areas. When applied directly to the micro-pitch copper pads of Micro LED driver circuit boards, the tin plating will be deposited indiscriminately on both the copper pad surface and non-pad areas, easily causing tin layer bridging and short circuits between adjacent copper pads, failing to meet the selective deposition requirements of micro-pitch arrays.
[0005] Furthermore, self-assembled monolayer technology has been used for selective surface treatment of large-size PCBs or semiconductor wafer-level devices, achieving selective deposition by forming a molecular-level barrier layer in the protected area. However, in Micro LED micro-pitch applications, the process compatibility between the molecular chain length, packing density, and pixel pitch of self-assembled monolayers is not yet clear. If a self-assembled monolayer with too short a chain length is selected, the film density is insufficient, and metal ions in the plating solution can easily penetrate the barrier layer, leading to unplated areas in non-pad regions. If a self-assembled monolayer with too long a chain length is selected, edge overlap is prone to occur at micro-pitch, increasing the risk of short circuits between adjacent copper pads. Existing technologies lack molecular chain length matching designs specifically for the micro-pitch characteristics of Micro LEDs, making it difficult to simultaneously achieve barrier performance and anti-overlap performance at the microscale.
[0006] Meanwhile, the deposition rate of a single electroless tin plating process is limited, making it difficult to obtain the target thickness of tin plating required for Micro LED chip bonding within a single process cycle. If a second electroless tin plating is performed directly, on the one hand, the surface of the primary plating layer is easily oxidized in air, forming a passivation layer that hinders the uniform initiation of the secondary deposition, leading to a decrease in plating thickness consistency; on the other hand, electroless tin plating is isotropic, and lateral growth during the secondary plating will further increase the bump diameter, exacerbating the bridging risk at micro-pitch levels. More importantly, existing secondary plating processes cannot retain the blocking activity of the original self-assembled monolayer, requiring the fabrication of a new masking layer to maintain selectivity, significantly increasing process complexity and cost. Therefore, how to achieve thickness uniformity and controllable lateral growth in the secondary plating while maintaining selective blocking has become an urgent technical problem to be solved. Summary of the Invention
[0007] The present invention provides a method for depositing tin solder on copper pads of a Micro LED driver circuit board in order to solve the problems existing in the prior art.
[0008] The technical solutions adopted in this invention are as follows:
[0009] A method for depositing solder on copper pads of a Micro LED driver circuit board includes the following steps:
[0010] S1: Provide a Micro LED driver circuit board substrate, the surface of which has a plurality of copper pads and the pixel spacing between adjacent copper pads is L;
[0011] S2: Perform chemical degreasing treatment on the substrate to remove oil stains from the surface of the copper pads;
[0012] S3: A self-assembled monolayer is coated on the entire surface of the substrate. The number of alkyl carbons in the self-assembled monolayer is positively correlated with the pixel pitch L: the smaller the pixel pitch L, the shorter the number of alkyl carbons in the selected self-assembled monolayer.
[0013] S4: Use acidic solution to etch and remove the oxide layer on the surface of the copper pad, so that the self-assembled monolayer in the copper pad area falls off along with the oxide layer, while the self-assembled monolayer in the non-pad area remains intact.
[0014] S5: Immerse the substrate treated in S4 into a chemical tin plating solution to deposit the first tin layer on the surface of the copper pads.
[0015] S6: The first tin layer is subjected to low-temperature aging treatment under an inert atmosphere. The treatment temperature is 180℃~200℃ and the treatment time is 10min~30min.
[0016] S7: The substrate after S6 is immersed in the chemical tin plating solution again. The self-assembled monolayer retained in the non-pad area is used for selective blocking. A second tin layer is deposited on the surface of the first tin layer to obtain a tin plating layer of the target height.
[0017] S8: Remove the self-assembled monolayer, followed by washing and drying.
[0018] Furthermore, in S3, when the pixel pitch L satisfies 15μm≤L<25μm, the number of alkyl carbons in the self-assembled monolayer is 8~12;
[0019] When the pixel pitch L satisfies 25μm≤L<50μm, the number of alkyl carbons in the self-assembled monolayer is 12~16;
[0020] When the pixel pitch L ≥ 50 μm, the number of alkyl carbons in the self-assembled monolayer is 16~18.
[0021] Furthermore, in S5 and S7, the chemical tin plating solution comprises a main salt, a complexing agent, a reducing agent, an antioxidant, and a pH adjuster; wherein,
[0022] The main salt is one of stannous chloride, stannous sulfate, or stannous methanesulfonate, with a concentration of 10-50 g / L;
[0023] The complexing agent is one or more of thiourea, citric acid or tartaric acid, with a concentration of 60~100g / L;
[0024] The reducing agent is sodium hypophosphite, with a concentration of 60~100g / L;
[0025] The antioxidant is either catechol or hydroquinone, with a concentration of 1-5 g / L.
[0026] The pH adjuster adjusts the pH value of the chemical tin plating solution to 0.5~2.
[0027] Furthermore, in S5 and S7, the chemical tin plating process temperature is 50℃~80℃, and the process time is 0.5h~2h.
[0028] Furthermore, between S6 and S7, a weak acid activation treatment is performed on the substrate after S6:
[0029] The oxide layer on the surface of the first tin layer is removed by immersing the sample in a 5% to 10% dilute sulfuric acid solution at room temperature for 30 to 60 seconds.
[0030] Furthermore, in S7, the chemical tin plating solution contains a leveling agent, benzyl acetone, at a concentration of 0.1~0.5 g / L, to suppress the lateral growth of the second tin layer at the edge of the copper pad.
[0031] Furthermore, in S8, the self-assembled monolayer is removed by oxygen plasma etching or immersion in organic solvents.
[0032] Furthermore, after S8, the process also includes heating the substrate to 240°C~260°C for reflow, causing the tin plating layer to shrink and form truncated spherical bumps.
[0033] Furthermore, in S2, the chemical degreasing treatment uses an alkaline solution containing alkaline components and surfactants. The concentration of the alkaline components is 20~80 g / L, the concentration of the surfactants is 0.2~2 g / L, the cleaning temperature is 50℃~80℃, and the soaking time is 10~30 min.
[0034] Furthermore, in S4, the acidic solution contains acidic components, the mass concentration of which is 10%~20%, the cleaning temperature is room temperature, and the soaking time is 0.5~3 minutes.
[0035] The present invention has the following beneficial effects:
[0036] (1) This invention employs a method of coating the entire surface of the substrate with a self-assembled monolayer, selectively removing the self-assembled monolayer in the copper pad area by acid pickling, and retaining the self-assembled monolayer in the non-pad area as a selective barrier layer. Subsequently, a tin plating layer is directly deposited on the copper pad surface using a chemical tin plating solution. This process eliminates the need for physical masks and alignment processes, fundamentally avoiding the alignment deviation problem between the mask opening and the copper pad, simplifying the process steps, reducing the cost of mask manufacturing and alignment equipment, and eliminating the defect of uneven solder paste filling caused by the reduction of the opening size, thereby improving the process yield of tin solder deposition on micro-pitch copper pads.
[0037] (2) The present invention uses the selective blocking effect of self-assembled monolayer to make the tin plating layer deposited only in the copper pad area, while the non-pad area is effectively blocked by the self-assembled monolayer, avoiding short circuit between adjacent copper pads and meeting the selective deposition requirements of Micro LED micro-pitch array.
[0038] (3) This invention establishes a positive correlation and hierarchical matching relationship between the number of alkyl carbons in the self-assembled monolayer and the pixel pitch: the smaller the pixel pitch, the shorter the number of alkyl carbons in the self-assembled monolayer is selected. At smaller pixel pitches, short-chain self-assembled monolayers can effectively suppress the risk of edge overlap and reduce the probability of short circuits between adjacent copper pads; at larger pixel pitches, long-chain self-assembled monolayers can improve the film density, enhance the blocking ability against metal ions in the plating solution, and prevent plating leakage in non-pad areas. Through the matching design of chain length and pitch, both anti-overlap performance and blocking performance are achieved at the microscale, expanding the process window of chemical tin plating in the Micro LED micro-pitch scenario.
[0039] (4) After the first tin layer is deposited by chemical tin plating, the crystal structure of the plating layer is stabilized by low-temperature aging treatment, while retaining the blocking activity of the self-assembled monolayer in the non-pad area. Then, it is immersed in the chemical tin plating solution again for secondary selective deposition to obtain a tin plating layer of the target thickness. The secondary plating process breaks through the thickness limitation of single chemical tin plating and meets the requirements of Micro LED chip soldering for tin plating thickness. Moreover, the secondary deposition does not require the preparation of a new masking layer and can still rely on the original self-assembled monolayer to maintain good deposition selectivity, with low process complexity.
[0040] (5) The present invention adds a weak acid activation treatment before the second plating, and uses dilute sulfuric acid solution to remove the oxide layer on the surface of the first tin layer without damaging the self-assembled monolayer in the non-pad area, thus ensuring the uniform start of the second deposition and the consistency of the initial plating rate; the addition of the leveling agent benzyl acetone to the second plating solution can inhibit the lateral growth of the tin plating layer at the edge of the copper pad, control the increase in bump diameter within the allowable range of micro-pitch, and effectively avoid the bridging risk in the second plating process.
[0041] (6) After removing the self-assembled monolayer, the present invention can shrink the tin plating layer to form truncated spherical bumps through reflow treatment. The bump height has good consistency and can meet the coplanarity requirements of the mass transfer of Micro LED. Attached Figure Description
[0042] Figure 1 The images show optical microscope comparisons of the copper pads on a Micro LED driver circuit board before and after chemical tin plating. The left image shows the exposed state of the copper pads before tin plating, while the right image shows the state of selective tin deposition on the surface of the copper pads after tin plating. No tin deposition was observed in the non-pad areas. Detailed Implementation
[0043] The invention will now be further described with reference to the accompanying drawings.
[0044] The Micro LED driver circuit board described in this embodiment includes an insulating substrate, the surface of which is distributed with a plurality of copper pads for soldering LED chips (e.g., ...). Figure 1 The pixel pitch between two adjacent copper pads is L, and the substrate surface outside the copper pads is an insulating oxide layer. Before solder deposition, the front-end process of the driver circuit board is completed first, so that the copper pads are exposed on the substrate surface, and the surface morphology and dimensional accuracy of the copper pads meet the requirements of Micro LED packaging.
[0045] Chemical degreasing is performed on the driver circuit board after the previous process to remove residual oil, organic impurities, and particulate contaminants from the copper pads, ensuring surface cleanliness. Chemical degreasing involves immersion in an alkaline solution containing alkaline components and surfactants. The alkaline components can be one or more of sodium hydroxide, potassium hydroxide, sodium carbonate, and sodium phosphate, with a total concentration controlled between 20 g / L and 80 g / L. The surfactants can be one or more of OP-10 and sodium dodecylbenzene sulfonate, with a concentration controlled between 0.2 g / L and 2 g / L. The solution temperature is maintained between 50°C and 80°C, and the substrate immersion time is 10 to 30 minutes. Through the saponification effect of the alkaline components and the emulsification effect of the surfactants, the oil layer on the copper pad surface is thoroughly removed. After degreasing, the substrate surface is rinsed with deionized water to remove any residual alkaline solution and prevent any impact on subsequent processes.
[0046] After degreasing and cleaning, the substrate undergoes a self-assembled monolayer coating treatment to form a uniform self-assembled monolayer across the entire surface of the substrate. The self-assembled monolayer is made of alkylsilane-based polymer materials, which can be adsorbed onto the insulating oxide layer on the substrate surface through chemical bonding to form a dense organic barrier layer.
[0047] The number of alkyl carbons in the self-assembled monolayer is selected based on the pixel pitch L of adjacent copper pads, generally following the principle that the smaller the pixel pitch, the shorter the number of alkyl carbons: when the pixel pitch is small, the lateral fluctuation range of the short-chain alkylsilane molecules is smaller, which can avoid overlapping at the edges of adjacent copper pads and causing short circuits in subsequent tin plating; when the pixel pitch is large, the molecular packing density of the long-chain alkylsilane is higher, and the blocking performance of plating solution ions is stronger, which can effectively suppress the missed plating in non-pad areas. Specifically:
[0048] When the pixel pitch L satisfies 15μm≤L<25μm, an alkylsilane with 8 to 12 alkyl carbons is selected;
[0049] When the pixel pitch L satisfies 25μm≤L<50μm, an alkylsilane with 12 to 16 alkyl carbons is selected;
[0050] When the pixel pitch L≥50μm, alkylsilanes with 16 to 18 alkyl carbons are selected.
[0051] The coating process can be carried out by immersion. The substrate is immersed in a prepared alkylsilane ethanol solution for 5 to 20 minutes at room temperature to allow the alkylsilane molecules to be fully adsorbed onto the substrate surface. After removal, the surface is purged with nitrogen to remove excess solution, and then baked at 100°C to 120°C to cure, so that the self-assembled monolayer forms a stable chemical bond with the substrate surface.
[0052] After the self-assembled monolayer is cured, the substrate is subjected to acid pickling and activation treatment. The acid pickling and activation is carried out by immersing the substrate in an acidic solution. The acidic solution can be prepared by one or more of sulfuric acid, hydrochloric acid, and acetic acid. The mass concentration of the acidic component is controlled between 10% and 20%. The treatment temperature is room temperature and the immersion time is 0.5 min to 3 min.
[0053] During the pickling process, the acidic solution first corrodes and removes the thin oxide layer on the surface of the copper pads, exposing the pure copper surface underneath. Since the self-assembled monolayers in the copper pad area are adsorbed onto the copper oxide layer surface, as the oxide layer is corroded and dissolved, the self-assembled monolayers in the copper pad area detach along with the oxide layer, exposing the catalytically active pure copper surface. In contrast, the self-assembled monolayers in the non-pad areas are directly bonded to the surface of the insulating oxide layer. These oxides are not corroded under acidic conditions, so the self-assembled monolayers in the non-pad areas remain intact and continue to function as ion barriers. This creates a difference in surface properties between the pad and non-pad areas, providing the necessary conditions for subsequent selective electroless tin plating. After pickling, the substrate surface is rinsed with deionized water to remove any remaining acidic solution until the pH of the rinsing water is neutral.
[0054] After pickling and activation, the substrate is immediately immersed in a chemical tin plating solution for the first tin layer deposition, forming the first tin layer on the exposed copper pads. The chemical tin plating solution contains a main salt, complexing agent, reducing agent, antioxidant, and pH adjuster, among which:
[0055] The main salt is one of stannous chloride, stannous sulfate, or stannous methanesulfonate, with a concentration of 10 g / L to 50 g / L, used to provide stannous ions required for the deposition reaction;
[0056] The complexing agent is selected from one or more of thiourea, citric acid, and tartaric acid, with a concentration of 60g / L to 100g / L, to complex stannous ions, maintain the stability of the plating solution, and prevent the hydrolysis and precipitation of stannous ions.
[0057] Sodium hypophosphite is selected as the reducing agent, with a concentration of 60 g / L to 100 g / L, to reduce stannous ions to metallic tin on the catalytic surface, thereby achieving autocatalytic deposition of the tin layer;
[0058] The antioxidant is either catechol or hydroquinone, with a concentration of 1 g / L to 5 g / L, used to inhibit the oxidation of tin ions in the plating solution to tetravalent tin, thereby extending the service life of the plating solution.
[0059] Sulfuric acid or ammonia is used as a pH adjuster to adjust the pH value of the plating solution to the range of 0.5 to 2, ensuring the reactivity and stability of the plating solution.
[0060] The first chemical tin plating process is controlled at a temperature of 50℃ to 80℃, with a deposition time of 0.5h to 2h. A first tin layer is uniformly deposited on the copper pad surface via an autocatalytic reduction reaction. The thickness of the first tin layer can be controlled by the deposition time. After deposition, the substrate is removed from the plating solution, and the surface is rinsed with deionized water to remove any remaining plating solution.
[0061] After the first tin plating and cleaning, the substrate is placed in an inert atmosphere oven for low-temperature aging treatment. Nitrogen or argon can be used as the inert atmosphere. The treatment temperature is controlled between 180°C and 200°C, and the treatment time is 10 to 30 minutes. Within this temperature range, the internal grains of the first tin layer will recover and recrystallize, releasing the internal stress generated during the plating deposition process, stabilizing the crystal structure of the plating, and reducing the risk of plating cracking and peeling during subsequent secondary tin plating. Simultaneously, this treatment temperature is below the thermal decomposition temperature of the alkylsilane self-assembled monolayer. Under the protection of the inert atmosphere, the self-assembled monolayer in the non-pad areas will not undergo thermal decomposition or peeling, maintaining its intact structure and selective blocking activity for tin ions, providing a masking basis for subsequent secondary selective tin plating.
[0062] After the low-temperature aging treatment, the substrate is cooled to room temperature in the furnace and then subjected to a weak acid activation treatment. A 5% to 10% (w / w) dilute sulfuric acid solution is used to immerse the substrate at room temperature for 30 to 60 seconds. This weak etching removes the thin oxide layer formed on the surface of the first tin layer during the low-temperature aging process, restoring the catalytic activity of the tin surface and ensuring a uniform initiation of the deposition reaction during the second tin plating, avoiding problems such as localized missed plating or uneven plating rates. Under these dilute acid concentrations and immersion time conditions, only the oxide layer on the tin surface is etched away, without damaging the self-assembled monolayer in non-pad areas, thus maintaining the effectiveness of selective barrier properties. After activation, the substrate surface is quickly rinsed with deionized water to remove any remaining dilute acid solution.
[0063] After the substrate has been activated by weak acid, it is immersed in chemical tin plating solution again for a second tin layer deposition. A second tin layer is formed on the surface of the first tin layer, and finally a tin plating layer of the target thickness is obtained.
[0064] The basic composition of the chemical tin plating solution used for the second tin plating is the same as that for the first tin plating. At the same time, a leveling agent, benzyl acetone, with a concentration of 0.1 g / L to 0.5 g / L, is added to the plating solution to adsorb onto the highly active areas at the edge of the tin plating layer, inhibit the lateral growth of the bump edges, reduce the expansion of the bump diameter during the second deposition process, and avoid bridging and short circuits in the tin plating layers of adjacent copper pads, thus meeting the deposition requirements of micro-pitch copper pads.
[0065] Since the non-pad area is still covered by a complete self-assembled monolayer, the tin ions in the plating solution cannot contact the surface of the insulating substrate below. Therefore, secondary deposition only occurs on the surface of the first tin layer, which has catalytic activity, maintaining good deposition selectivity.
[0066] The temperature for the second electroless tin plating is also controlled between 50℃ and 80℃. The thickness of the second tin layer can be precisely controlled by adjusting the deposition time, ensuring that the total thickness of the final tin plating layer reaches the target value, and the uniformity of the plating thickness can be controlled within ±5%. After the second deposition is completed, the substrate is removed from the plating solution, and the surface is thoroughly cleaned with deionized water to remove any remaining plating solution components.
[0067] After secondary tin plating and cleaning, the residual self-assembled monolayer on the substrate surface is removed. Removal methods include oxygen plasma etching, which decomposes the organic self-assembled monolayer through oxidation by oxygen plasma; the processing time is adjusted according to the plasma power, typically 5 to 15 minutes. Alternatively, organic solvent immersion can be used, immersing the substrate in organic solvents such as acetone, ethanol, or toluene, followed by ultrasonic treatment to dissolve and peel off the self-assembled monolayer. After complete removal of the self-assembled monolayer, the substrate is rinsed multiple times with ultrapure water to thoroughly remove residual organic impurities and ionic contaminants. Subsequently, the substrate surface is purged with high-purity nitrogen or dried at a low temperature in an oven at 60°C to 80°C to obtain a clean Micro LED driver circuit board with a uniform tin plating.
[0068] After drying, the substrate can be further processed by reflow soldering. The substrate is placed in a reflow soldering machine and heated to 240°C to 260°C under a nitrogen protective atmosphere. This causes the tin plating on the copper pads to completely melt and shrink under the action of surface tension to form a truncated spherical tin plating, providing a uniform soldering interface for the subsequent mass transfer and soldering of Micro LED chips.
[0069] The above process was used to deposit solder on a Micro LED driver circuit board with a pixel pitch of 20μm. Alkyl silane with 10 carbon atoms was selected as the self-assembled monolayer material. After reflow soldering, the average height of the solder plating layer was 5μm with a height deviation of less than ±4%. There was no obvious plating failure in the non-pad area and no bridging short circuit between adjacent pads. The overall yield was improved by more than 15% compared with the traditional mask solder paste printing process, which can meet the process requirements of high-density Micro LED packaging.
[0070] The above description is only a preferred embodiment of the present invention. It should be noted that those skilled in the art can make several improvements without departing from the principle of the present invention, and these improvements should also be considered within the scope of protection of the present invention.
Claims
1. A method for depositing solder on copper pads of a Micro LED driver circuit board, characterized in that: Includes the following steps: S1: Provide a Micro LED driver circuit board substrate, the surface of which has a plurality of copper pads and the pixel spacing between adjacent copper pads is L; S2: Perform chemical degreasing treatment on the substrate to remove oil stains from the surface of the copper pads; S3: A self-assembled monolayer is coated on the entire surface of the substrate. The number of alkyl carbons in the self-assembled monolayer is positively correlated with the pixel pitch L: the smaller the pixel pitch L, the shorter the number of alkyl carbons in the selected self-assembled monolayer. S4: Use acidic solution to etch and remove the oxide layer on the surface of the copper pad, so that the self-assembled monolayer in the copper pad area falls off along with the oxide layer, while the self-assembled monolayer in the non-pad area remains intact. S5: Immerse the substrate treated in S4 into a chemical tin plating solution to deposit the first tin layer on the surface of the copper pads. S6: The first tin layer is subjected to low-temperature aging treatment under an inert atmosphere. The treatment temperature is 180℃~200℃ and the treatment time is 10min~30min. S7: The substrate after S6 is immersed in the chemical tin plating solution again. The self-assembled monolayer retained in the non-pad area is used for selective blocking. A second tin layer is deposited on the surface of the first tin layer to obtain a tin plating layer of the target height. S8: Remove the self-assembled monolayer, followed by washing and drying.
2. The method for depositing solder on copper pads of a Micro LED driver circuit board as described in claim 1, characterized in that: In S3, when the pixel pitch L satisfies 15μm≤L<25μm, the number of alkyl carbons in the self-assembled monolayer is 8~12. When the pixel pitch L satisfies 25μm≤L<50μm, the number of alkyl carbons in the self-assembled monolayer is 12~16; When the pixel pitch L ≥ 50 μm, the number of alkyl carbons in the self-assembled monolayer is 16~18.
3. The method for depositing solder on copper pads of a Micro LED driver circuit board as described in claim 1, characterized in that: In S5 and S7, the chemical tin plating solution comprises a main salt, a complexing agent, a reducing agent, an antioxidant, and a pH adjuster; wherein, The main salt is one of stannous chloride, stannous sulfate, or stannous methanesulfonate, with a concentration of 10-50 g / L; The complexing agent is one or more of thiourea, citric acid or tartaric acid, with a concentration of 60~100g / L; The reducing agent is sodium hypophosphite, with a concentration of 60~100g / L; The antioxidant is either catechol or hydroquinone, with a concentration of 1-5 g / L. The pH adjuster adjusts the pH value of the chemical tin plating solution to 0.5~2.
4. The method for depositing solder on copper pads of a Micro LED driver circuit board as described in claim 3, characterized in that: In S5 and S7, the chemical tin plating process temperature is 50℃~80℃ and the process time is 0.5h~2h.
5. The method for depositing solder on copper pads of a Micro LED driver circuit board as described in claim 1, characterized in that: Between S6 and S7, a weak acid activation treatment is also performed on the substrate after S6: The oxide layer on the surface of the first tin layer is removed by immersing the sample in a 5% to 10% dilute sulfuric acid solution at room temperature for 30 to 60 seconds.
6. The method for depositing solder on copper pads of a Micro LED driver circuit board as described in claim 1 or 5, characterized in that: In S7, the chemical tin plating solution contains a leveling agent, benzyl acetone, at a concentration of 0.1~0.5 g / L, which is used to suppress the lateral growth of the second tin layer at the edge of the copper pad.
7. The method for depositing solder on copper pads of a Micro LED driver circuit board as described in claim 1, characterized in that: In S8, the self-assembled monolayer is removed by oxygen plasma etching or immersion in organic solvents.
8. The method for depositing solder on copper pads of a Micro LED driver circuit board as described in claim 1 or 7, characterized in that: Following S8, the process also includes heating the substrate to 240°C~260°C for reflow, causing the tin plating to shrink and form truncated spherical bumps.
9. The method for depositing solder on copper pads of a Micro LED driver circuit board as described in claim 1, characterized in that: In S2, the chemical degreasing treatment uses an alkaline solution containing alkaline components and surfactants. The concentration of the alkaline components is 20~80 g / L, and the concentration of the surfactants is 0.2~2 g / L. The cleaning temperature is 50℃~80℃, and the soaking time is 10~30 min.
10. The method for depositing solder on copper pads of a Micro LED driver circuit board as described in claim 1, characterized in that: In S4, the acidic solution contains acidic components with a mass concentration of 10% to 20%, the cleaning temperature is room temperature, and the soaking time is 0.5 to 3 minutes.